Does smoking protect against osteoarthritis? Meta-analysis of observational studies. Issue 7 (7th April 2011) - Hui, Michelle; Doherty, Michael; Zhang, Weiya
Abstract : Objectives: To determine whether smoking is protective against the development of osteoarthritis (OA). Methods: Observational studies for the association between smoking and OA were systematically searched through Medline (1950–), Embase (1980–), Web of Science (1960–), PubMed, Google and relevant references. ORs and 95% CIs were directly retrieved or calculated. Current standards for reporting using MOOSE were followed. Quality-related aspects such as study design, setting, sample selection and confounding bias were recorded. Stratified and meta-regression analyses were undertaken to examine the covariates. Results: Of 48 studies (537 730 participants) identified from the systematic literature search, 8 were cohort, 21 cross-sectional and 19 case–control. There was an overall negative association between smoking and OA (OR=0.87; 95% CI 0.80 to 0.94) and subgroup analysis confirmed this in case–control studies (OR=0.82; 95% CI 0.70 to 0.95), but not in cohort (OR=0.92; 95% CI 0.81 to 1.06) or cross-sectional studies (OR=0.89; 95% CI 0.78 to 1.01). Within case–control studies a negative association occurred only in hospital settings (OR=0.65; 95% CI 0.52 to 0.81), not in community settings (OR=0.90; 95% CI 0.75 to 1.08). The association was also seen in knee OA, radiographic OA and smoking as a secondary exposure (covariate or confounding factor). Meta-regression analysis demonstrated that a hospital setting and smoking as a secondary exposure were the major source of the negative association. Conclusions: The protective effect of smoking in OA observed in some epidemiological studies is likely to be false. It may be caused by selection bias, often in a hospital setting where control subjects have smoking-related conditions and studies that are not primarily designed to investigate smoking. Critical appraisal of such studies is needed.